A phase-1 trial of linsitinib (OSI-906) in combination with bortezomib and dexamethasone for the treatment of relapsed/refractory multiple myeloma. Issue 7 (7th June 2021) - Khan, Sahar; LeBlanc, Richard; Gyger, Martin; White, Darrell; Kaufman, Johnathan; Jazubowiak, Andrzej; Gul, Engin; Paul, Harminder; Le, Lisa W.; Lau, Anthea; Li, Zhihua; Trudel, Suzanne
Abstract: We report results of a phase-1 study evaluating the safety and anti-cancer activity of the small molecule insulin-like growth factor-1 receptor (IGF-1R) inhibitor, linsitinib combined with bortezomib, and dexamethasone in relapsed/refractory multiple myeloma. Nineteen patients were enrolled across four dose-escalation cohorts (75–150 mg bid). The maximum tolerated dose of linsitinib was 125 mg. The most frequent Grade 3/4 AEs occurring in ≥10% of patients were thrombocytopenia (53%), bone pain (26%), neutropenia (21%), diarrhea (14%), anemia (14%), rash (10%), and lung infection (10%). Study discontinuation due to treatment-related AEs was low (16%). Across all cohorts the ORR was 61% (95% CI: 28.9–75.6%). Three partial response or greater and one stable disease were observed in proteasome inhibitor (PI) refractory patients ( n  = 5). Median PFS was 7.1 months (95% CI: 3.6–NA). Linsitinib plus bortezomib and dexamethasone demonstrate a manageable safety profile while the clinical benefit particularly in PI refractory patients warrants further exploration.